2002
DOI: 10.1890/1051-0761(2002)012[0456:smcadw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Salt Marsh Canopy Architecture Differs With the Number and Composition of Species

Abstract: In response to the debate about how ecosystem functions are affected by species richness vs. species composition, we explored canopy architecture (plant cover, height, and layering) in three contexts: a reference marsh, a field experiment, and a greenhouse experiment. Species‐rich canopies (five or more species) in the reference marsh were taller and had more (13 vs. 7) layers than monotypes of Salicornia virginica, although both had 100% cover. Cover and layering were greater for three‐ and six‐species plots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 53 publications
4
35
0
Order By: Relevance
“…It has a central tidal channel and two adjacent tidal plains, all excavated from disturbed upland in 1996 to connect a natural tidal channel to a tidal lagoon. The south tidal plain was planted to test BEF theory (Keer and Zedler 2002) as follows. In April of 1997, we established 87 2 3 2 m experimental plots with assemblages of 0, 1 (solos), 3 (trios), or 6 (sextets) native salt marsh plant species drawn from the eight native species that are common to the marsh plain of Tijuana Estuary and were known to cooccur at small spatial scales (often in 0.25-m 2 monitoring quadrats).…”
Section: Site Description and Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a central tidal channel and two adjacent tidal plains, all excavated from disturbed upland in 1996 to connect a natural tidal channel to a tidal lagoon. The south tidal plain was planted to test BEF theory (Keer and Zedler 2002) as follows. In April of 1997, we established 87 2 3 2 m experimental plots with assemblages of 0, 1 (solos), 3 (trios), or 6 (sextets) native salt marsh plant species drawn from the eight native species that are common to the marsh plain of Tijuana Estuary and were known to cooccur at small spatial scales (often in 0.25-m 2 monitoring quadrats).…”
Section: Site Description and Experimental Setupmentioning
confidence: 99%
“…All seedlings were grown from Tijuana Estuary seed for five months in greenhouse flats before planting (Keer and Zedler 2002), and each 2 3 2 m plot was planted with exactly 90 seedlings to avoid selection effects arising from differential establishment (Huston 1997). Because our assemblages were randomly chosen, the total number or seedlings planted varied slightly from species to species (low ¼ 755, high ¼ 885; Fig.…”
Section: Site Description and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…New techniques for reestablishing plants are needed for sites that impose severe stress on seedlings. Earlier experiments showed that species-rich plantings in salt marsh restorations can promote recruitment (Lindig-Cisneros and Zedler 2002), increase canopy complexity (Keer and Zedler 2002) and enhance rates of biomass and nitrogen accumulation (Callaway et al 2003); however, to promote diverse vegetation on severe sites, it might be necessary to manipulate the topography (Boeken and Shachak 1994;Whisenant 2002), plant in clusters (MacMahon 1997) and/or amend the soil to ameliorate stress on newly establishing vegetation (Handa and Jefferies 2000;Callaway 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Such species will likely require active introduction by restoration practitioners to achieve reference site levels of native species diversity. Achieving greater native plant diversity in restored marshes will conserve native biodiversity and increase wetland ecosystem services, such as habitat complexity and nitrogen accumulation (Zedler et al 2001;Keer & Zedler 2002;Callaway et al 2003;), making it an increasingly endorsed restoration evaluation metric (Zedler et al 2001;Peterson & Lipcius 2003).…”
Section: Discussionmentioning
confidence: 99%